Large-volume paracentesis with indwelling peritoneal catheter and albumin infusion: a community hospital study. Issue 5 (1st January 2016) - Martin, Daniel K.; Walayat, Saqib; Jinma, Ren; Ahmed, Zohair; Ragunathan, Karthik; Dhillon, Sonu
Abstract : Background: The management of ascites can be problematic. This is especially true in patients with diuretic refractory ascites who develop a tense abdomen. This often results in hypotension and decreased venous return with resulting renal failure. In this paper, we further examine the risks and benefits of utilizing an indwelling peritoneal catheter to remove large-volume ascites over a 72-h period while maintaining intravascular volume and preventing renal failure. Methods: We retrospectively reviewed charts and identified 36 consecutive patients undergoing continuous large-volume paracentesis with an indwelling peritoneal catheter. At the time of drain placement, no patients had signs or laboratory parameters suggestive of spontaneous bacterial peritonitis. The patients underwent ascitic fluid removal through an indwelling peritoneal catheter and were supported with scheduled albumin throughout the duration. The catheter was used to remove up to 3 L every 8 h for a maximum of 72 h. Regular laboratory and ascitic fluid testing was performed. All patients had a clinical follow-up within 3 months after the drain placement. Results: An average of 16.5 L was removed over the 72-h time frame of indwelling peritoneal catheter maintenance. The albumin infusion utilized correlated to 12 mg/L removed. The average creatinine trend improved in a statistically significant manner from 1.37 on the day of admission to 1.21 on the day of drain removal. No patients developed renal failure during the hospital course. There were no documented episodes of neutrocytic ascites or bacterial peritonitis throughout the study review. Conclusion: Large-volume peritoneal drainage with an indwelling peritoneal catheter is safe and effective for patients with tense ascites. Concomitant albumin infusion allows for maintenance of renal function, and no increase in infectious complications was noted.